2021
DOI: 10.1101/2021.03.04.21252903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of remdesivir on 28 day mortality in hospitalized patients with COVID-19: February 2021 Meta-analysis

Abstract: Background: The COVID-19 pandemic has stimulated worldwide investigation into a myriad of potential therapeutic agents, including antivirals such as remdesivir. The first RCT reporting results on the impact of remdesivir on COVID-19 in a peer reviewed journal was the ACTT-1 trial published in November, 2020. The ACTT-1 trial showed more rapid clinical improvement and a reduced risk of 28-day mortality in patients who received remdesivir. This study is a meta-analysis of peer reviewed RCTs aims to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Yet, many clinicians remain skeptical of remdesivir's benefits. A recent meta-analysis study of randomized controlled trials demonstrates no statistically significant evidence of reduced mortality in hospitalized COVID-19 patients when treated with remdesivir [129]. On 19 November 2020, WHO recommended against using remdesivir.…”
Section: Remdesivirmentioning
confidence: 99%
“…Yet, many clinicians remain skeptical of remdesivir's benefits. A recent meta-analysis study of randomized controlled trials demonstrates no statistically significant evidence of reduced mortality in hospitalized COVID-19 patients when treated with remdesivir [129]. On 19 November 2020, WHO recommended against using remdesivir.…”
Section: Remdesivirmentioning
confidence: 99%
“…We included 36 reviews of remdesivir [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] plus two major living reviews of all treatments for COVID-19 [ 25 , 26 ] (collectively reported in 45 publications up to May 20, 2021). The first review was published on April 30, 2020 [42] , the day after the first randomized trial of remdesivir and the preliminary findings of two other trials were published.…”
Section: Resultsmentioning
confidence: 99%
“…Yet many clinicians remain skeptical of remdesivir's benefits. A recent meta-analysis study of randomized controlled trials demonstrates no statistically significant evidence of reduced mortality in hospitalized COVID patients when treated with Remdesivir [121]. On Nov19 2020, WHO recommended against using remdesivir.…”
Section: Remdesivirmentioning
confidence: 99%